Parliamentary Opposition and Legislative Proposals: A Study of Institutional Constraints on The Role of The Moroccan Opposition - Hicham Nassar (Journal of Law and Social Politics, 2026)
Aligned with more advanced constitutional democracies, the Moroccan Constitution of 2011 expanded the powers of Parliament, particularly the House of Representatives. It also reinforced the rights of the opposition by granting it multiple legal powers and privileges that extend beyond the typical limits of representative democracy based on proportional representation. This framework allows the opposition to hold constitutional powers that position it between the majority and minority groups, granting it a distinct status that enables meaningful participation in parliamentary decision-making. The opposition plays a vital role in the legislative process, as emphasized in the Constitution, notably through the inclusion of its proposed laws on the agendas of both parliamentary chambers. At least one day each month is dedicated to reviewing draft laws, including those submitted by the opposition. A particularly prominent role of the parliamentary opposition in the House of Representatives is its chairmanship of the Justice, Legislation, and Human Rights Committee, alongside its leadership of another permanent committee not specified in the House’s internal regulations. This arrangement is based on the provisions of the second paragraph of Article 10 and the third paragraph of Article 69 of the Constitution. Despite the significance of these provisions, some researchers argue that they do not necessarily ensure the opposition an influential position in the legislative process.